Faktor-Faktor Yang Memengaruhi Profitabilitas Pada Perusahaan Manufaktur - Agnes Tania, Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This study aims to obtain empirical evidence regarding the effect of liquidity, leverage, total asset turnover, firm size, and sales growth toward profitability in manufacturing companies listed on Indonesia Stock Exchange during 2017-2019. This study uses 37 companies as the research sample selected using purposive sampling method with a total of 111 data for three years. The data processing technique uses multiple linear regression assisted by EViews 11 program. The results of this study indicate that total asset turnover has a positive effect on profitability, leverage has a negative effect on profitability, while liquidity, firm size, and sales growth have no effect on profitability. The implication of this study is the need to increase total asset turnover and reduce leverage to increase company profitability which will provide good signals for investors.